Type 2 diabetes mellitus and the risk of male infertility: a Mendelian randomization study - Zhu, Xiao-Bin; Niu, Zhi-Hong; Fan, Wei-Min; Sheng, Chang-Sheng; Chen, Qian (Frontiers in Endocrinology, 2023)
Objective: To assess the causal effect of type 2 diabetes mellitus (T2DM) on male infertility (MI) and erectile dysfunction (ED) by Mendelian randomization (MR) analysis.Methods: Data for T2DM, MI, and ED were obtained from genome-wide association studies (GWAS) involving 298, 957, 73, 479, and 223, 805 Europeans, respectively. We performed univariate MR analysis using MR Egger, Weighted median (WM) and Inverse variance weighted (IVW) methods to assess causal effects among the three.Through the Genotype Tissue Expression (GTEx) database, single-nucleotide polymorphisms (SNPs) that affect the expression levels of T2DM-related genes were located using expression quantitative trait loci (eQTL).Results: MR analysis showed a significant causal relationship between T2DM and